Investigation the effect of a herbal composition based on blackseed on patients with primary hypothyroidism: A randomized controlled trial - Najmeh Javidi; Zahra Mazloum Khorasani; Roshanak Salari; Shabnam Niroumand; Mahdi Yousefi (Mashhad University of Medical Sciences, 2024)
Objective: Hypothyroidism is characterized by insufficient production of thyroxine by the thyroid gland. Levothyroxine may not fully alleviate patients' symptoms. This study aimed to assess the impact of a herbal product on weight, body mass index (BMI), thyroid hormones, lipid profile, fasting blood sugar (FBS), depression, and quality-of-life scores in patients.Materials and Methods: 72 patients with primary hypothyroidism, aged between 20 and 65 years old, participated in the trial and they were randomly allocated into two groups. The intervention group received the herbal powder containing Trachyspermum ammi L., Nigella sativa L., and Citrus aurantifolia L. while the control group received Avicel for 8 weeks.Results: Treatment with the herbal product resulted in statistically significant reductions in anthropometric variables such as BMI (p=0.03), hip circumference (HC) (p=0.008), waist circumference (WC) (p<0.001), and waist-to-hip circumference ratio (WHR) (p=0.003) in the intervention group in comparison between intervention and control groups. However, the decrease in weight was not statistically significant (p=0.08) in the intervention group compared the control group. In comparison between two groups, the depression score exhibited a statistically significant decrease in the intervention (p=0.001) and control groups (p=0.01), while there was a statistically significant increase in the quality-of-life score only in the intervention group (p<0.001) in comparison between intervention and control groups.Conclusion: The results indicate the potential beneficial effects of the herbal product on anthropometric variables in patients. Furthermore, the intervention yielded significant improvements in depression symptoms and quality-of-life scores among the patients.